2018
DOI: 10.1167/iovs.18-23786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitric Oxide onAcanthamoeba castellanii

Abstract: Our results demonstrated the anti-Acanthamoeba effect of exogenous NO. This finding suggests that NO-releasing drug platforms, including nano-carriers, can be a promising therapeutic strategy for Acanthamoeba keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“… 13 15 Exogenous delivery of NO by adding NO donors, sodium nitrite (NaNO 2 ) and sodium nitroprusside (SNP), in planktonic cultures of A. castellanii demonstrated that killing Acanthamoeba was concentration dependent for both trophozoite and cyst forms. 11 However, we also found that the anti- Acanthamoeba effect and human corneal epithelial cell (HCEC) toxicity were proportional: NaNO 2 showed a weak anti- Acanthamoeba effect and less corneal epithelial toxicity, while SNP showed a strong anti- Acanthamoeba effect and severe HCEC toxicity. 11 …”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“… 13 15 Exogenous delivery of NO by adding NO donors, sodium nitrite (NaNO 2 ) and sodium nitroprusside (SNP), in planktonic cultures of A. castellanii demonstrated that killing Acanthamoeba was concentration dependent for both trophozoite and cyst forms. 11 However, we also found that the anti- Acanthamoeba effect and human corneal epithelial cell (HCEC) toxicity were proportional: NaNO 2 showed a weak anti- Acanthamoeba effect and less corneal epithelial toxicity, while SNP showed a strong anti- Acanthamoeba effect and severe HCEC toxicity. 11 …”
Section: Introductionmentioning
confidence: 85%
“… 11 However, we also found that the anti- Acanthamoeba effect and human corneal epithelial cell (HCEC) toxicity were proportional: NaNO 2 showed a weak anti- Acanthamoeba effect and less corneal epithelial toxicity, while SNP showed a strong anti- Acanthamoeba effect and severe HCEC toxicity. 11 …”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Acanthamoeba keratitis is among the most intractable of corneal infectious diseases leading to blindness ( 107 ). Recently, Yim et al ( 108 ) demonstrated the anti-Acanthamoeba effect using NO donors.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide coated with SiNPs showed toxicity on corneal epithelial cells at 100 µg/mL. (Yim et al, 2018) Nanoemulsions Coumarin rich Pterocaulon balansae (methanol extract)…”
Section: A Castellaniimentioning
confidence: 99%